Ability of different matrices to transmit African swine fever virus. (27th April 2021) - ,; Nielsen, Soren Saxmose; Alvarez, Julio; Bicout, Dominique Joseph; Calistri, Paolo; Canali, Elisabetta; Drewe, Julian Ashley; Garin‐Bastuji, Bruno; Gonzales Rojas, Jose Luis; Gortázar Schmidt, Christian; Herskin, Mette; Miranda Chueca, Miguel Ángel; et al.
Abstract: This opinion assesses the risk posed by different matrices to introduce African swine fever virus (ASFV) to non‐affected regions of the EU. Matrices assessed are feed materials, enrichment/bedding materials and empty live pigs transport vehicles returning from affected areas. Although the risk from feed is considered to be lower than several other pathways (e.g. contact with infected live animals and swill feeding), it cannot be ruled out that matrices assessed in this opinion pose a risk. Evidence on survival of ASFV in different matrices from literature and a public consultation was used in an Expert Knowledge Elicitation (EKE) on the possible contamination of products and traded or imported product volumes used on pig farms. The EKE results were used in a model that provided a risk‐rank for each product's contamination likelihood ('q'), its trade or import volume from affected EU or Eurasian areas (N) and the modelled number of potentially infected pig farms (N × q). The products ranking higher regardless of origin or destination were mash and pelleted compound feed, feed additives and cereals. Bedding/enrichment materials, hydrolysed proteins and blood products ranked lowest regardless of origin or destination. Empty vehicles ranked lower than compound feed but higher than non‐compound feed or bedding/enrichment material. It is very likely (95–99% certainty) that compound feed and cereals rank higher than feed materials, which rank higher than bedding/enrichment material and forage. As this is an assessment based on several parameters including the contamination and delivery to a pig farm, all of which have the same impact on the final ranking, risk managers should consider how the relative rank of each product may change with an effective storage period or a virus inactivation step. Abstract : This publication is linked to the following EFSA Supporting Publications articles: http://www.efsa.europa.eu/en/supporting/pub/9993e and http://www.efsa.europa.eu/en/supporting/pub/9994e